2016
DOI: 10.1007/s10157-016-1233-4
|View full text |Cite|
|
Sign up to set email alerts
|

Dietary intake in Japanese patients with kidney transplantation

Abstract: Changes in daily diet of the patients with dialysis and kidney transplantation were recognized. The patients who received kidney transplantation would take daily diet according to their renal function although they do not have specific standards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The number of patients undergoing renal transplantation therapy has increased in recent years. The number is thought to be approximately 10,000 people, but diet therapy for this group of patients has not been discussed sufficiently [ 3 ]. In any case, it has become possible for humans to avoid death by ESKD using these three methods.…”
Section: Introductionmentioning
confidence: 99%
“…The number of patients undergoing renal transplantation therapy has increased in recent years. The number is thought to be approximately 10,000 people, but diet therapy for this group of patients has not been discussed sufficiently [ 3 ]. In any case, it has become possible for humans to avoid death by ESKD using these three methods.…”
Section: Introductionmentioning
confidence: 99%
“…High intakes of vitamin K have been observed in China, where men consume 242 µg/day and women 239 µg/day [ 37 ]. Nagaoka et al investigated the diet of KTx patients in Japan and reported a total vitamin K intake of 299 ± 196 µg/day [ 38 ], while our study shows that KTx patients consume the amounts of vitamin K1 recommended for the general population but insufficient amounts of vitamin K2. It should be emphasized that, so far, there are no recommendations for vitamin K1 and K2 consumption in KTx populations; however, it is recognized that a diet rich in these vitamins may slow down the progression of vascular and bone abnormalities [ 5 , 6 , 7 ].…”
Section: Discussionmentioning
confidence: 50%
“…In general, KT has some advantages in the improvement of life expectancy and QoL compared with dialytic therapies [14,15]. In fact, in contrast to peritoneal dialysis and hemodialysis, limitation of amount of drinking water and excessive dietary restriction are necessary the patients received KT when transplanted renal graft achieves normal function [16]. In addition, concentrations of uremic toxins in patients with KT are remarkably lower than those dialysis patients even though technology of dialysis is improving [17].…”
Section: Introductionmentioning
confidence: 99%